2018
DOI: 10.1177/2045894018763682
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing improves genetic testing accuracy in pulmonary artery hypertension

Abstract: Sanger sequencing, the traditional “gold standard” for mutation detection, has been wildly used in genetic testing of pulmonary artery hypertension (PAH). However, with the advent of whole-exome sequencing (WES), few studies have compared the accuracy of WES and Sanger sequencing in routine genetic testing of PAH. PAH individuals were enrolled from Fu Wai Hospital and Shanghai Pulmonary Hospital. WES was used to analyze DNA samples from 120 PAH patients whose bone morphogenetic protein receptor type 2 (BMPR2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Further, PVOD represents poor prognosis such that the current mean time for diagnosis to death and first symptom to death are 14.3 ± 19.3 and 24.7 ± 24.8 months [15]. Likewise, our patient underwent an aggressive disease phenotype in a shorter timeline that Whole exome sequencing is one of the most prominent next generation sequencing technology, which is widely used in understanding the genetic etiology of a disease; provides an advantage that all genes driving the disease could be investigated in a robust, cheaper and high throughput fashion [20]. With the advancement of technology, the cost of data analysis and interpretation associated with whole exome sequencing has dropped as low as USD 500 per sample; the genetic testing application has rapidly evolved and genetic testing/counseling has been increasing available in many PAH centers [21,22].…”
Section: Discussionmentioning
confidence: 95%
“…Further, PVOD represents poor prognosis such that the current mean time for diagnosis to death and first symptom to death are 14.3 ± 19.3 and 24.7 ± 24.8 months [15]. Likewise, our patient underwent an aggressive disease phenotype in a shorter timeline that Whole exome sequencing is one of the most prominent next generation sequencing technology, which is widely used in understanding the genetic etiology of a disease; provides an advantage that all genes driving the disease could be investigated in a robust, cheaper and high throughput fashion [20]. With the advancement of technology, the cost of data analysis and interpretation associated with whole exome sequencing has dropped as low as USD 500 per sample; the genetic testing application has rapidly evolved and genetic testing/counseling has been increasing available in many PAH centers [21,22].…”
Section: Discussionmentioning
confidence: 95%
“…However, Tenorio et al reported that the EIF2AK4 mutation c.3344C > T (p. P1115 L) caused an early onset of disease and low survival rate in six consanguineous PVOD patients [ 8 ]. Another report of a case of an EIF2AK4 mutation at c.4833_4836dup (p. Q1613Kfs*10), reported that this mutation caused an aggressive phenotype, such that the time from onset of disease symptoms to death was less than 6 months [ 28 ]. We are surprised to note that all of those patients who responded well to PAH-targeted therapies had the EIF2AK4 mutation located in the degenerate kinase-like domain (amino acids between 280 and 537), while the aggressive phenotype mutation is located at the HisRS domain (amino acids between 1021 and 1492) or C-terminal (amino acids between 1492 and 1648) [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25] In the analyses of practice gaps 5 and 7, additional published data related to methodology dependent FN, false-positive, or true-positive rates were used. 15,20,22,[25][26][27][28][29][30][31][32][33][34][35] Furthermore, in the analyses of practice gaps 5 and 7, additional third-party real-time laboratory data from US-based laboratories were used to supplement the Medicare claims data and laboratory test results data (eg, test performance and positivity rates) included in the Diaceutics repository. A total of 5,589 patients with aNSCLC newly diagnosed in 2019 were identified within the real-time laboratory data set.…”
Section: Data Source and Populationmentioning
confidence: 99%